Enhancement of Physical Characteristics of Styrene–Acrylonitrile Nanofiber Membranes Using Various Post-Treatments for Membrane Distillation - Reza Sallakhniknezhad; Manijeh Khorsi; Ali Sallakh Niknejad; Saeed Bazgir; Ali Kargari; Mohsen Sazegar; Mohsen Rasouli; Soryong Chae (Membranes, 2021)
Insufficient mechanical strength and wide pore size distribution of nanofibrous membranes are the key hindrances for their concrete applications in membrane distillation. In this work, various post-treatment methods such as dilute solvent welding, vapor welding, and cold-/hot-pressing processes were used to enhance the physical properties of styrene–acrylonitrile (SAN) nanofiber membranes fabricated by the modified electrospinning process. The effects of injection rate of welding solution and a working distance during the welding process with air-assisted spraying on characteristics of SAN nanofiber membranes were investigated. The welding process was made less time-consuming by optimizing system parameters of the electroblowing process to simultaneously exploit residual solvents of fibers and hot solvent vapor to reduce exposure time. As a result, the welded SAN membranes showed considerable enhancement in mechanical robustness and membrane integrity with a negligible reduction in surface hydrophobicity. The hot-pressed SAN membranes obtained the highest mechanical strength and smallest mean pore size. The modified SAN membranes were used for the desalination of synthetic seawater in a direct contact membrane distillation (DCMD). As a result, it was found that the modified SAN membranes performed well (>99.9% removal of salts) for desalination of synthetic seawater (35 g/L NaCl) during 30 h operation without membrane wetting. The cold-/hot-pressing processes were able to improve mechanical strength and boost liquid entry pressure (LEP) of water. In contrast, the welding processes were preferred to increase membrane flexibility and permeation.